Strategic Planning of Marketing Activity in Enterprises - Rakhmatullaeva Nargiza Oktyabrevna (Periodica Journal, 2023)
In the article, enterprises tend to conduct their activities efficiently and use the method of strategic planning in advance in order to obtain high profits for an ever longer period of time. Based on the analysis of changes in the market and directions of scientific and technological development, general goals are determined, which are the basis for developing the company's strategy. The company's strategy reflects the main program of activity, the primary direction and distribution of resources in the field of marketing, finance, organizational activities, personnel policy and other areas.
Keywords: market; profits; activities; determined